Analisis Segmentasi Pasar Konsumen Jamu Madura Berdasarkan Aspek Perilaku (Studi Kasus Pada Konsumen Jamu "Sumber Madu" di Kelurahan Demangan Kecamatan Bangkalan Kabupaten Bangkalan Madura). - Fakhry, Muhammad; Jakfar, Abdul Aziz; Yayuk, Sri (Rekayasa, 2008)
Marke·tsegmentation defined as market determination as sub.;.class consumer owning requirement and desire which is much the same to, becoming sub-class which can be reached withthedifferent marketing hotchpotch. ClusterAnalysis is a statistical technique todissociate objects became a certain group which is each other data analysis constructively knowable SPSS so that clusters deputizing consumer segment Madura. Result Klastering from research show have beenformed by 7clusterfrom entireall responder (100) people, among other things is: (1) cluster 1, is very paying attention to group of quality and security in purchase of goods, (2). cluster 2,group taking afancy tojamu Madura, but they remain to price, (3) cluster 3, isgroup which not take asproblem of the price in buying jamu Madura, (4) cluster 4, is group taking afancy tojamu Madura and there is desire to consume the jamu of Madura a more regular again and this group is not fanatical to certain j amu's brand, (5) cluster 5,group.which enough take afancy to thejamu Madura and they desire toconsume thejamu of Madura a more regular, (6) cluster 6, is represent taking afancy to jamu Madura and they buy thejamu alsofor thepresent of existingfamil y outside Bangkalan and to be resold and (7) cluster 7, this group take a fancy to the jamu Madura but in buying their not require the suggestionfrom famil y member orfrom others.